Development and Evaluation of the Effectiveness of a Sexual Communication Model Counseling Package on the Satisfaction and Sexual Intimacy of Iranian Couples - Javad Vakili; Seyed Ali Kimiaei; Hossein Kareshki; Seyed Amir AminYazdi (Sadra medical sciences journal, 2023)
Introduction: Sexual satisfaction is considered one of the most important factors in marital happiness, and it plays a significant role in the health, well-being, and overall quality of life for individuals in a society. Therefore, the research aims to develop and assess the effectiveness of a counseling package based on the sexual communication model on the level of satisfaction and sexual intimacy in Iranian couples.Methods: The research was conducted using a mixed exploratory research design. Initially, qualitative methods were employed to identify the factors influencing couples' sexual exchange. Subsequently, a counseling package was developed based on these factors. For the purpose of quantitative validation, the relative content validity ratio and content validity index were utilized. In the next research phase, an applied and semi-experimental method with a pre-test and post-test design was employed, including a one-month follow-up with a control group. Data analysis was carried out using repeated measures analysis of variance (ANOVA) and the SPSS software version 26.Results: The results showed that the relative content validity coefficient and content validity index were higher than the required size (CVR≥49 and CVI≥79) and a valid counseling package was prepared. The results of the next stage also showed that the sexual communication pattern counseling package significantly increased sexual satisfaction (P<0.01) and sexual intimacy (P<0.01); the experimental group had a significant increase in sexual satisfaction and intimacy compared to the control group.Results: The results indicated that the content validity ratio and content validity index exceeded the required thresholds (CVR≥0.49 and CVI≥0.80), establishing the validity of the counseling package. Subsequently, the results of the next phase demonstrated that the sexual communication pattern counseling package significantly contributed to sexual satisfaction (P<0.01) and sexual intimacy (P<0.01). The experimental group exhibited a substantial increase in sexual satisfaction and intimacy compared to the control group.Conclusion: The counseling package based on the sexual communication pattern is valid and can lead to an increase in the sexual satisfaction and intimacy of Iranian couples.